Leveraging narrative images through environmental degradation messages for environmental awareness in Kafanchan City, Nigeria/ Timothy Titus, Nurul Hanim Romainoor and Muhammad Uzair Ismail - Titus, Timothy; Romainoor, Nurul Hanim; Ismail, Muhammad Uzair (Universiti Teknologi MARA, Perak, 2024)
The environment in Kafanchan, Nigeria deteriorates daily due to human factors such as refuse dumping, bush burning, deforestation, and open grazing. Narrative Images have been acknowledged to significantly impact molding perceptions, attitudes, and behaviours across many fields. This article explores the potential of narrative images as a compelling tool for raising environmental awareness. Narrative images, such as photographs, are essential in communicating and addressing environmental issues, engaging audiences, and motivating positive action. This study aims to raise environmental awareness in Kafanchan, Nigeria by leveraging narrative images. The study is committed to capture photographs that depict the various environmental problems in Kafanchan City, Nigeria and to evaluate the impact of images in conveying environmental degradation messages. Photography was used as a method to capture images that depict environmental concerns in Kafanchan City, Nigeria, analysed using visual narrative method. The images used for this study were selected using inclusion and exclusion criteria. The photographs categorised into bush burning, deforestation, and refuse dumping, erosion, open grazing and poster pasting. Interview was used to get the opinion of the respondents about the impact of images in conveying environmental degradation messages. Most of the participants rated the images to have a very strong and strong impact. However, 14.30% believed images 4, 9 and 11 had a weak impact. 7.10% also believed images 6 and 7 have a weak impact. The authors argue that leveraging narrative images for environmental awareness is an effective medium in visual communication.